Cross-sectional characterization of electrodeposited, monocrystalline Au Nanowires in parallel arrangement - Schneckenburger, Manuel; Spatz, Joachim P.; Rustom, Amin (Small, 2012)
Cross-sections of cylindrically shaped nanowires are fabricated using a focused ion beam technique. They are oriented such that the electron beam direction is parallel to a low-index zone axis for high- resolution imaging. In this configuration the direction of gold nanowire growth can be determined using electron diffraction.